2017
DOI: 10.1016/j.drugalcdep.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural examination of college drinking culture in Spain, Argentina, and USA: Measurement invariance testing of the College Life Alcohol Salience Scale

Abstract: Objective: Perceptions about what is "normal" drinking in college, measured by the College Life Alcohol Salience Scale (CLASS; 15 items), have been robustly associated with elevated levels of problematic alcohol use, yet the role of these beliefs has not been studied outside the U.S. The present work examined measurement invariance of the CLASS across sex, drinker status, and in individuals of three different countries (i.e., U.S., Argentina, and Spain).Additional goals were to evaluate differences on the CLAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Although several studies have demonstrated that beliefs about the perceived centrality of alcohol use to the college experience are robustly associated with alcohol outcomes (Bravo et al, 2017a;Osberg et al, 2010Osberg et al, , 2011Osberg et al, , 2012, this study builds from a smaller number of studies to demonstrate that the beliefs about the perceived centrality of marijuana use to the college experience are robustly associated with marijuana outcomes (Pearson et al, 2017(Pearson et al, , 2018. The internalization of college alcohol/marijuana use culture has been shown to mediate the effects of sensation seeking and impulsivity on alcohol/marijuana outcomes (Bravo et al, 2018a;Hustad et al, 2014;Pearson et al, 2018), and the present study shows that PBS mediates the effects of these beliefs on alcohol/marijuana outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have demonstrated that beliefs about the perceived centrality of alcohol use to the college experience are robustly associated with alcohol outcomes (Bravo et al, 2017a;Osberg et al, 2010Osberg et al, , 2011Osberg et al, , 2012, this study builds from a smaller number of studies to demonstrate that the beliefs about the perceived centrality of marijuana use to the college experience are robustly associated with marijuana outcomes (Pearson et al, 2017(Pearson et al, , 2018. The internalization of college alcohol/marijuana use culture has been shown to mediate the effects of sensation seeking and impulsivity on alcohol/marijuana outcomes (Bravo et al, 2018a;Hustad et al, 2014;Pearson et al, 2018), and the present study shows that PBS mediates the effects of these beliefs on alcohol/marijuana outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Age at fi rst use was assessed with two items: How old were you the fi rst time you: (a) drank alcohol and (b) used marijuana. College alcohol beliefs were assessed using a 12-item version (Bravo et al, 2017a) of the College Life Alcohol Salience Scale (Osberg et al, 2010). College marijuana beliefs were assessed using the 8-item Perceived Importance of Marijuana to the College Experience Scale (Pearson et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Já no consumo de cannabis, os estudantes com maiores níveis de comportamentos de consumo de risco, são os que: apresentam comportamentos binge-drinking; consomem atualmente tabaco; e apresentam maiores motivos de consumos etílicos. Estas associações estatisticamente significativas, entre o consumo de diferentes substâncias, poderão ser explicadas pelos resultados verificados por Bravo et al, 56 onde se observaram associações significativas entre as crenças relativas ao consumo de álcool, como parte da experiência académica, com os diferentes motivos de consumos etílicos (avaliado pelo DMQ-R) e com os consumos do tipo binge-drinking.…”
Section: Discussionunclassified
“…Despite similar initial level of drug exposure, some adolescents will progress to alcohol use disorders (AUD), whereas others will keep a controlled use. Ethanol use is almost normative by the end of high school, in most western countries (Bravo et al., 2017), yet AUD, which peaks at ages 16–24, affects 7%–12% of the population (Schramm‐Sapyta, Walker, Caster, Levin, & Kuhn, 2009).…”
Section: Introductionmentioning
confidence: 99%